Efforts of Online Business to Achieve Effectiviness with management Information System - Tutupary, Sweeta Elfonsia; Aldianto, Leo (Journal of Business and Management, 2014)
Along with the rapid growing technological advances in many areas of life, allowing the public to enjoy the convenience that is generated by the technology. One example of technology developed at this time is in the field of information technology. Today, information systems provide the communication and analytic power that firms need for conducting trade and managing business on a global scale. Controlling the far-flung global corporation-communicating with distributors and suppliers, operating 24 hours a day in different national environments, servicing local and international reporting needs-is a major business challenge that requires powerful information system responses. To become effective and profitable participants in international markets, firms need powerful information and communication systems. Information systems are needed to optimize the flow of information and knowledge within the organization and to help management maximize the firmâ€™s knowledge resources.This study aims to know how the online business achieves effectiveness and efficiency by using management information system. By using information system, how the online business can improve their business process. In this research, the researcher analysis several online business. Some of them already using information system and most of them are not using information system. From this online business, researcher finds some differences in their business process model. To analysis the problem of online businesses, researcher using business process model and information system to identify some aspects that affect the effectivity and efficiency of business process. This research shows thWat the online business that has been using information system can increase customer satisfaction, improved quantity and quality of information, improve operational efficiency and flexibility, improved quality of internal and external communications, improved quality of planning, and improved quality control and supervision. For the implementation,Â  for the online business that not using information system can be start using information system and also re-engineering business process can help the online business to be more effective. By re-engineering business process, the cycle time of the business process can be reducing so the process could be more effective.Keywords: Online business, Management Information System, Business process model, computer-based information systems.